The evolving role of accountants as consultants: essential skills for success in a dynamic business environment - Che Hassan, Anita; Nik Wil, Nor Jaslina (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2024)
Today accountants are being viewed as not just bookkeepers, but consultants who help with strategic decision making. Several elements are contributing to this evolution, from technological advancements and regulatory updates through the increasing reliance on data-driven intelligence by developing some expertise in more technical, project-based areas along with skills related to strategic thinking as well upon improving communication and handling better clients’, accountants can be the best tech consultant ever. While businesses must continue to navigate global uncertainty and rapid change, the function of accountants as trusted advisors is more important than ever. In this article, we will discuss the 7 skills which are essential for an accountant to adopt if he or she is looking forward to being a consultant. We start by discussing how technical competence, strategic planning and communication matters. The discussion then moves on to managing client relationships, providing in-depth services as well as the importance of keeping up with industry trends. Most importantly, we highlight the importance of ethics and integrity as part of the main criteria in becoming a successful accountant. Tech-Savvy: Accountants should scale up their technical skills Today, technical expertise is about more than accounting duties alone. In this era of big data, accountants cum consultants must also be proficient in modern financial modeling and new emerging technologies like artificial intelligence (AI) and blockchain. As the accounting field gets more digitized, accountants who are well versed with cloud based accounting software and automation tools can offer their clients solutions that are accurate to a great extent and in real time. Technology competency allows accountants to shift from their historical role as mere recorder of transactions, into the broader arena of providing strategic advice that underpins business decision-making (Jackson & Leon 2021). Modern consulting practices rely heavily on AI and data analytics. In the end, accountants who are equipped with these technologies can provide predictive analysis and financial forecasting capabilities to help businesses take proactive action (Morales & Ventura, 2020). That means, they are no longer bookkeepers doing simple reconciliations and journal entries, because these technical skills enable accountants to be forward-leaning advisors who can address complex business strategies by utilizing data available to them.